Cascade of Deoxyribozymes for the Colorimetric Analysis of Drug Resistance in Mycobacterium tuberculosis - Dhar, Bidhan C. (Biosens Bioelectron, 2020)
A visual cascade detection system has been applied to the detection and analysis of drug-resistance profile of Mycobacterium tuberculosis complex (MTC), a causative agent of tuberculosis. The cascade system utilizes highly selective split RNA-cleaving deoxyribozyme (sDz) sensors. When activated by a complementary nucleic acid, sDz releases the peroxidase-like deoxyribozyme apoenzyme, which, in complex with a hemin cofactor, catalyzes the color changes of the sample’s solution. The excellent selectivity of the cascade has allowed for the detection of point mutations in the sequences of the MTC rpoB, katG, and gyrA genes, which are responsible for resistance to rifampin, isoniazid, and fluoroquinolone, respectively. When combined with isothermal nucleic acid sequence based amplification (NASBA), the assay was able to detect amplicons of 16S rRNA and katG mRNA generated from 0.1 pg and 10 pg total RNA taken for NASBA, respectively, in less than 2 h, producing a signal detectable with the naked eye. The proposed assay may become a prototype for point-of-care diagnosis of drug resistant bacteria with visual signal output.